Deliberation in Constitutional Amendment: Reappraising Ireland's Deliberative Mini-Publics. (17th September 2020) - Doyle, Oran; Walsh, Rachael
Abstract : Deliberative democracy innovations in constitutional amendment processes – Ireland's experimentation with deliberative mini-publics on constitutional issues – Factors influencing the political take-up of recommendations – The significance of the support of the legislative majority –Deliberative mini-publics as an accountability mechanism.